Factors associated with breastfeeding at six months postpartum in a group of Australian women - McLachlan Helen L; Forster Della A; Lumley Judith (BMC, 2006)
Abstract Background Despite high levels of breastfeeding initiation in Australia, only 47 percent of women are breastfeeding (exclusively or partially) six months later, with marked differences between social groups. It is important to identify women who are at increased risk of early cessation of breastfeeding. Methods Data from the three arms of a randomised controlled trial were pooled and analysed as a cohort using logistic regression to identify which factors predicted women continuing to feed any breast milk at six months postpartum. The original trial included 981 primiparous women attending a public, tertiary, women's hospital in Melbourne, Australia in 1999-2001. The trial evaluated the effect of two mid-pregnancy educational interventions on breastfeeding initiation and duration. In the 889 women with six month outcomes available, neither intervention increased breastfeeding initiation nor duration compared to standard care. Independent variables were included in the predictive model based on the literature and discussion with peers and were each tested individually against the dependent variable (any breastfeeding at six months). Results Thirty-three independent variables of interest were identified, of which 25 qualified for inclusion in the preliminary regression model; 764 observations had complete data available. Factors remaining in the final model that were positively associated with breastfeeding any breast milk at six months were: a very strong desire to breastfeed; having been breastfed oneself as a baby; being born in an Asian country; and older maternal age. There was an increasing association with increasing age. Factors negatively associated with feeding any breast milk at six months were: a woman having no intention to breastfeed six months or more; smoking 20 or more cigarettes per day pre-pregnancy; not attending childbirth education; maternal obesity; having self-reported depression in the six months after birth; and the baby receiving infant formula while in hospital. Conclusion In addition to the factors commonly reported as being associated with breastfeeding in previous work, this study found a negative association between breastfeeding outcomes and giving babies infant formula in hospital, a high maternal body mass index, and self-reported maternal depression or anxiety in the six months after the baby was born. Interventions that seek to increase breastfeeding should consider focusing on women who wish to breastfeed but are at high risk of early discontinuation.